MENENTUKAN KEDALAMAN DAN KETEBALAN AKUIFER DENGAN METODE LOGGING TAHANAN JENIS PADA WAKTU PENGEBORAN AIR TANAH - Yuningsih, Sri M. (JURNAL SUMBER DAYA AIR, 2018)
The aim of this resistivity logging measurement is to decide the stratification of rock and distribution of aquifer based on the resistivity value. The objective of the well logging is to determine the depth and thickness of aquifer for well construction, in order to decide the position of screen in the aquifers .Interpretation results of the resistivity logging of aquifer of sand and sandy tuff vary between 20 – 40 ohm-m and 60 – 115 ohm-m for breccia. Groundwater in the Ciparay and Cibodas areas is predicted in the depth of 42 – 66 m and 75 – 108 m, consisting of intercalation of young volcanic fan and Bandung lake deposit. The aquifer in Dago area is less than 100 m deep representing young volcanic deposit including the Cibeureum Formation, whereas aquifers with a depth of more than 100 m comprise volcanic deposit, including the Cikapundung Formation. It is recommended to extract groundwater from more than 50 m deep, in order to prevent influence to phreatic aquifer as excavated well. The minimum kind of well logging for groundwater drilling should consist of resistivity, self-potential and gamma ray logging.